Effect of worksheet scaffolds on student learning in problem-based learning. - Choo SS; Rotgans JI; Yew EH; Schmidt HG; Choo, Serene S Y; Rotgans, Jerome I; Yew, Elaine H J; Schmidt, Henk G (Advances in Health Sciences Education, 2011)
The purpose of this study was to investigate the effect of worksheets as a scaffolding tool on students' learning achievement in a problem-based learning (PBL) environment. Seventeen PBL classes (N = 241) were randomly assigned to two experimental groups-one with a worksheet provided and the other without. Students' learning of the topic at hand was evaluated by comparing results from pre- and post-lesson concept recall tests. We also obtained information about students' perceptions of factors impacting their learning using a Learning Impact Questionnaire. The data was analyzed by means of analyses of variance. Results of the study indicated that there was no statistically significant difference between the levels of understanding for both groups of students. In addition, survey results revealed that the strongest factor perceived by students to impact their learning in a PBL context is the tutor followed by team and class dynamics, while the influence of the worksheet was rated lowest. These findings suggest that scaffolds such as worksheets may not play a significant role in enhancing students' learning within the social constructivist framework of problem-based learning. On the other hand, the importance of the role of tutor and collaborative small group learning which are key features of PBL is reinforced.